2020
DOI: 10.1002/wrna.1631
|View full text |Cite
|
Sign up to set email alerts
|

Intron retention and its impact on gene expression and protein diversity: A review and a practical guide

Abstract: Intron retention (IR) occurs when a complete and unspliced intron remains in mature mRNA. An increasing body of literature has demonstrated a major role for IR in numerous biological functions, including several that impact human health and disease. Although experimental technologies used to study other forms of mRNA splicing can also be used to investigate IR, a specialized downstream computational analysis is optimal for IR discovery and analysis. Here we provide a review of IR and its biological implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 120 publications
0
29
0
Order By: Relevance
“…Intron retention also can occur in linear sequences. It acts to increase protein isoform diversity [ 64 ] and enables rapid responses by delaying splicing until the protein product is required [ 65 ]. As discussed below, introns also can be processed to produce cytoplasmic dsRNA [ 66 ].…”
Section: The Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Intron retention also can occur in linear sequences. It acts to increase protein isoform diversity [ 64 ] and enables rapid responses by delaying splicing until the protein product is required [ 65 ]. As discussed below, introns also can be processed to produce cytoplasmic dsRNA [ 66 ].…”
Section: The Backgroundmentioning
confidence: 99%
“…Only recently have the technical challenge to fully documenting the extent and consequences of these noncanonical RNA processing pathways been solved. How they alter the dsRNAome and MDA5 activation is currently unresolved [ 64 , 67 ].…”
Section: The Backgroundmentioning
confidence: 99%
“…Intron retention is characterized by the inclusion of one or more introns in mature mRNA transcripts and has been previously considered to be an artefact of a dysfunctional spliceosome. It is known that alternative splicing, including intron retention, is frequent during embryonic development and contribute not only to the plasticity of the transcriptome but also the regulation of gene expression and protein diversity (Revil et al, 2010;Kalsotra and Cooper, 2011;Grabski et al, 2021). Here, we showed that intron retention is a landmark of the FLC transcriptome.…”
Section: Alternative Splicing: High Intron Retention In Flcsmentioning
confidence: 71%
“…Overall, we showed that intron retention is a landmark of the FLC transcriptome. It is known that alternative splicing is frequent during embryonic development, usually cell/organ specific and plays a role in gene expression regulation and protein diversity ( Revil et al, 2010 ; Kalsotra and Cooper, 2011 ; Grabski et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intron retention is characterized by the inclusion of one or more introns in mature mRNA transcripts and has been previously considered to be an artifact of a dysfunctional spliceosome. It is known that alternative splicing, including intron retention, is frequent during embryonic development and contribute not only to the plasticity of the transcriptome but also the regulation of gene expression and protein diversity ( Revil et al, 2010 ; Kalsotra and Cooper, 2011 ; Grabski et al, 2021 ). Here, we showed that intron retention is a landmark of the FLC transcriptome.…”
Section: Discussionmentioning
confidence: 99%